Knowledge, Attitude, Action, Ability to Pay (ATP), and Willingness to Pay (WTP) Young Adults in Fulfilling the Need for Oral Hygiene Maintenance - NadyaSavira Giyansyah; Nadia Chairony; Indira Arella Harianto; Ulfie Rahmah Aliyah; AryoDwipoKusumo (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: One of the preventive efforts that can be performed to avoid dental and oral health problemsis by maintaining oral hygiene. Currently, there are various tools for maintaining dental and oral hygienethat are sold in the market. Purpose: To reveal the knowledge, attitude, action, Ability to Pay (ATP), andWillingness to Pay (WTP) of young adults in fulfilling the need for maintenance of oral hygiene. Methods:This research was a descriptive research type. The sample size was determined as 100 people, targeting thegroup of young adults aged 20-29 years who have worked or earn. A cross tabulation test was conductedbetween the ATP and WTP variables with demographic characteristics, namely age and work experience.Results: Based on the age frequency of ATP sufferers, those aged 20-29 years are able to meet the needs oforal hygiene at most at a cost of Rp. 51,000- Rp. 100,000, and the age frequency with the most WTP at a costof Rp. 141,000 - Rp. 160,000.Based on the length of time working with the ATP, most of the oral hygieneneeds are Rp. 51,000-Rp. 100,000. Meanwhile, the frequency of working with WTP is the maximum cost ofRp. 141,000 - Rp. 160,000. Conclusion: According to the research results, it can be concluded that the levelof knowledge, attitude, and action of young adults in fulfilling the needs for maintenance of oral hygiene isgood.